Hepatic Artery Ligation for Arterial Rupture Following Liver Transplantation: A Reasonable Option. Issue 4 (7th February 2013) - Boleslawski, E.; Bouras, A. F.; Truant, S.; Liddo, G.; Herrero, A.; Badic, B.; Audet, M.; Altieri, M.; Laurent, A.; Declerck, N.; Navarro, F.; Létoublon, C.; et al.
Abstract : Hepatic artery (HA) rupture after liver transplantation is a rare complication with high mortality. This study aimed to review the different managements of HA rupture and their results. From 1997 to 2007, data from six transplant centers were reviewed. Of 2649 recipients, 17 (0.64%) presented with HA rupture 29 days (2–92) after transplantation. Initial management was HA ligation in 10 patients, reanastomosis in three, aorto‐hepatic grafting in two and percutaneous arterial embolization in one. One patient died before any treatment could be initiated. Concomitant biliary leak was present in seven patients and could be subsequently treated by percutaneous and/or endoscopic approaches in four patients. Early mortality was not observed in patients with HA ligation and occurred in 83% of patients receiving any other treatment. After a median follow‐up of 70 months, 10 patients died (4 after retransplantation), and 7 patients were alive without retransplantation (including 6 with HA ligation). HA ligation was associated with better 3‐year survival (80% vs. 14%; p = 0.002). Despite its potential consequences on the biliary tract, HA ligation should be considered as a reasonable option in the initial management for HA rupture after liver transplantation. Unexpectedly, retransplantation was not always necessary after HA ligation in this series. Abstract : In some patients, hepatic artery ligation may be the right life‐saving option to achieve long‐term survival.